THE EFFECTIVENESS OF GEOGEBRA-ASSISTED PROBLEM BASED LEARNING ON STUDENTS’ MATHEMATICAL LITERACY IN SOLID GEOMETRY - Anggun Nurfaadilla; Rahma Nasir; Mustamin Idris; I Nyoman Murdiana (JME (Journal of Mathematics Education), 2026)
This study aimed to examine the effectiveness of the Problem-Based Learning (PBL) model assisted by GeoGebra on students’ mathematical literacy skills in solid geometry. The research employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The population consisted of ninth-grade students at a junior high school in Palu, and the sample was selected using cluster random sampling. Data were collected through essay tests to measure students’ mathematical literacy skills. Data analysis was conducted using the independent sample t-test and N-gain analysis at a significance level of 0.05. The results showed that the Sig. (2-tailed) value was 0.001, indicating a statistically significant difference between the experimental and control groups. The average N-gain score in the experimental class was 0.46, which falls into the moderate category and is higher than that of the control class, which was 0.15 in the low category. These findings indicate that the Problem-Based Learning (PBL) model assisted by GeoGebra is effective in improving students’ mathematical literacy skills in solid geometry and can be used as an alternative instructional approach in mathematics learning.